Estimation of salivary neopterin in chronic periodontitis - Little Mahendra; Jaideep Mahendra; Sai Krishna Borra; Aishwarya Nagarajan (Wolters Kluwer Medknow Publications, 2014)
Background: Periodontal diseases are the most common bacterial infection predominantly associated with Gram-negative microorganisms that exist in the subgingival biofilm. Analysis of saliva provides a noninvasive means of evaluating the role of the host response in periodontal disease. Though salivary enzymes can be used as the biomarkers, neopterin has been recently used as one of the important diagnostic tools in the field of periodontics. Hence, we aimed to identify the neopterin levels in unsimulated saliva from the chronic periodontitis patients and compare them with the periodontally healthy subjects. Materials and Methods: Twenty subjects participated in the study and were categorized as the experimental group (chronic periodontitis patients) and control groups (healthy subjects). Unstimulated saliva samples were collected from both the groups for neopterin estimation. Neopterin in saliva was estimated using Shimadzu High Performance Liquid Chromatography with LC-20AD pump system, equipped with RF-10 AXL fluorescence detector. Statistical Analysis Used: Data were expressed as mean ± SD and analyzed using GraphPad Prism version 6.0 (California, USA). Statistical analysis was done by Student's t-test Results: The neopterin level in unstimulated saliva was found to be higher in the experimental group than the control group with P ≤ 0.05. Conclusions: The chronic periodontitis patients showed higher neopterin level in unstimulated saliva as compared to control. Hence, neopterin can be used as a potential biomarker for identification of the periodontal disease in its initial stage can help in preventing the disease progression.